Mindfulness training for individuals in organisations: application, adaptation and perceived value - Kantor, Linda Sara (Graduate School of Business (GSB), 2019)
Recently, mindfulness training has garnered increasing interest from organizational practitioners and scholars. This research explores participants’ applications, experiences, and perceived impact of mindfulness for those who have undergone training outside of the workspace. Kabat-Zinn’s approach to Mindfulness-Based Interventions (MBIs) underpins and informs this research. I conducted semi-structured interviews with 53 participants working in a variety of organisational contexts. Participants had trained in one of three different MBIs: an 8-week Mindfulness-Based Stress Reduction Programme (MBSR), a two-year Mindful Leadership Programme as part of an Executive MBA programme, or a two-year Mindfulness Certification for professionals. Using an interpretive phenomenological approach and thematic analysis, I explored ways in which participants applied and shared mindfulness practice at work and home. I present the results in the form of an inductive model of mindfulness in the workplace. I distinguish some key individual meta-capacities (awareness of the wandering mind, embodiment, equanimity and kindness) and capacities developed (resilience, sense-of-self, multiple perspectives and possibility). I highlight how mindfulness enhanced the ability to work with difficult emotions, thoughts and sensations, opening participants up to new modes of relationship and new framings of productivity and power in the workplace. The transformation in the areas of productivity, power and relationality, could be tied in with the Buddhist concept of three poisons; greed (excessive productivity), hatred (competitive and aggressive workplace behaviours) and delusion (use and abuse of power at work). Mindfulness provides an antidote. The voices of participants highlight the intra and interpersonal effects and the potential and challenges of mindfulness practice in organisational contexts. This research offers some hopeful data and a deeper understanding of the potential of mindfulness training as a modality for transformation in the workplace. It offers this at a time where some critics question whether the use of mindfulness to improve work-life might lead to dilution and misappropriation of the practice. The model developed in this study contributes to Positive Organisational Scholarship (POS) literature and provides a map of how mindfulness might be of value in the workplace in the service of wisdom and compassion.